Defoliator Pest to Caboclos and Gourmet Food to the Suruí Indians: Contrasting Amazonian Perspectives of Lusura sp. Caterpillars - Carlos E. A. Coimbra (Ethnobiology Letters, 2012)
The use of a Lusura sp. (Lepidoptera: Notodontidae) caterpillar as food by the Suruí Indians from the southwestern Brazilian Amazon is reported in the context of family collecting excursions during arboreal infestations observed in July-August 1983. This caterpillar erupts in very large numbers on Brazil nut trees, denuding them of foliage. The paper calls attention to contrasting views about these caterpillar infestations among different inhabitants of the forest, being considered a desirable food delicacy by the Suruí and a destructive pest defoliator by caboclos.